Sigesbeckia orientalis L. Extract Alleviated the Collagen Type II–Induced Arthritis Through Inhibiting Multi-Target–Mediated Synovial Hyperplasia and Inflammation - Linghu, Ke-Gang; Xiong, Shi Hang; Zhao, Guan Ding; Zhang, Tian; Xiong, Wei; Zhao, Mingming; Shen, Xiang-Chun; Xu, Wei; Bian, Zhaoxiang; Wang, Yitao; Yu, Hua (Frontiers in Pharmacology, 2020)
Excessive proliferation and inflammation of synovial fibroblasts accelerate and decorate the pathological process of rheumatoid arthritis (RA). Sigesbeckia orientalis L. (SO) is one of the main plant sources for Sigesbeckiae Herba (SH) which has been used traditionally in treating various forms of arthritis and rheumatic pain. However, the anti-arthritic mechanisms of SO are still not clearly understood. In this study, we investigated the therapeutic effects and the underlying mechanisms of SO against collagen type Ⅱ (CⅡ)-induced RA in rats as well as the interleukin (IL)-1β-induced human synovial SW982 and MH7A cells. For the in vivo studies, thirty-six Wistar male rats were randomly arranged to 6 groups based on the body weight, and then CⅡ-induced to RA model for 15 days, followed by treatment with the 50% ethanolic extract of SO (SOE, 0.16, 0.78 and 1.56 g / kg) for 35 days. The results suggested that SOE significantly inhibited the formation of pannus (synovial hyperplasia to the articular cavity) and attenuated the cartilage damaging and bone erosion in the CIA-induced rats’ hind paw joints. Moreover, SOE decreased the production of C-reactive protein (CRP) in the serum and the expression of IL-6 and IL-1β in the joint muscles, as well as recovered the decreased regulatory T lymphocytes. The results obtained from the in vitro studies showed that SOE (50, 100 and 200 μg/mL) not only inhibited the proliferation, migration and invasion of human synovial SW982 cells but also decreased the IL-1β-induced expression of IL-6 and IL-8 both in SW982 and MH7A cells. Besides, SOE reduced the expression of COX-2, NLRP3 and MMP9, and increased the expression of MMP2 in the IL-1β-induced SW982 cells. Furthermore, SOE blocked the activation of NF-κB and reduced the phosphorylation of MAPKs and the expression of AP-1. In conclusion, SOE attenuated the CⅡ-induced RA through inhibiting of MAPKs/NF-κB/AP-1-mediated synovial hyperplasia and inflammation.